Trustworthy Cloud Storage - (:unkn) unknown (My University, 2025)
Cloud Computing offers its users centralized and inexpensive computing services, facilitating the development of large and scalable applications. Despite the advent of cloud computing, many individuals and companies are reluctant to entrust the cloud with their data. We briefly describe three “nightmare” scenarios that illustrate typical concerns and which discourage wider adoption of cloud computing services: Malicious users. An employee of a cloud provider secretly installs software in the cloud servers to mine the data from commercial users. This software is carefully disguised as part of a set of complex monitoring scripts. He then silently sells the stolen information to competitors for profit. Software bugs. After accidentally uploading incriminating data to the cloud, a user quickly submits a deletion request, which completes successfully. Unfortunately, an unknown bug in the cloud software stack causes data deletion actions to fail silently in rare occasions. The incriminating data is left on the cloud and is later found by a cloud provider system administrator. Low performance. Following a positive media report, a cloud provider increases computing resources to accommodate a growing number of users. A decision is made to expand the infrastructure with higher-end hardware, which was chosen after in-house testing. However, when the new hardware is put in production, it underperforms in certain scenarios. The provider struggles with a publicity nightmare, with users quickly moving to alternative providers. The “nightmare” scenarios above demonstrate the need for secure, verifiable and robust services for storing data on the cloud. Our goal in this proposal is to invent broadly applicable concepts that address similar scenarios to those. In particular, we propose to (a) design a secure cloud data storage system; (b) develop unique tools that advance the state-of-the-art for profiling and validating applications running on the cloud; (c) integrate new hardware storage technologies that improve overall performance for cloud storage; (d) devise techniques to predict the performance of a cloud application; and (e) create new mechanisms that allow cloud providers to augment their infrastructure seamlessly. We will implement all concepts as part of a prototype, hopefully encouraging cloud providers to adopt similar concepts in their commercial offerings. This adoption will allow reluctant communities to take advantage of the opportunities created by cloud computing. We expect our work to become influential both in academia and industry, particularly within sectors that are an important part of the Swiss industrial sector.
Keywords: Cloud Computing; Data; Trust; Security; Robustness; Verifiability; Prototype; Cloud Storage